Resource allocation and budgetary mechanisms for decentralized health systems: experiences from Balochistan, Pakistan - Andrew Green; B. Ali; A. Naeem; D. Ross (The World Health Organization, 2000)
This paper identifies key political and technical issues involved in the development of an appropriate resource allocation and budgetary system for the public health sector, using experience gained in the Province of Balochistan, Pakistan. The resource allocation and budgetary system is a critical, yet often neglected, component of any decentralization policy. Current systems are often based on historical incrementalism that is neither efficient nor equitable. This article describes technical work carried out in Balochistan to develop a system of resource allocation and budgeting that is needs-based, in line with policies of decentralization, and implementable within existing technical constraints. However, the development of technical systems, while necessary, is not a sufficient condition for the implementation of a resource allocation and decentralized budgeting system. This is illustrated by analysing the constraints that have been encountered in the development of such a system in Balochistan.